The importance of digital skills for the Western Balkans -comparative analysis between the Western Balkans and the European Union - Nikola Levkov; Bojan Kitanovikj (Economy, Business and Development: An International Journal (EB&D), 2024)
In knowledge-intensive economies, skills emerged as crucial resources, determining economic development. Thus, in the post-pandemic, digital world, digital skills gain new ground, attracting the interest of researchers and practitioners. As one of the first studies on the topic in the region, the article aims to investigate the level of digital, computer, and skills in evaluating data, information, and digital content in Western Balkans (WB) and to compare it with the European Union (EU) region. Furthermore, we found that EU countries are way ahead in terms of basic or above basic overall digital skills on average. In the WB context, Serbia and Montenegro are close to converging with the EU average related to computer skills while Montenegro and North Macedonia lead in skills in evaluating data, information, and digital content. The results point out that the level of digital skills highly correlates with labor productivity and GDP per capita in WB.
Keywords: J24; 330; comparative analysis; digital skills; European Union; labor productivity; Western Balkans